Politics and Islam at the age of nationalism: the conception of Pan-Islamism and the issue of the caliphate in Russia and Turkey - Akhmetova, Elmira (IIUM Press, International Islamic University Malaysia, 2017)
This book examines the accuracy of the so-called "universal sociological theory" of Hans Kohn on the examples of identity consciousness of Russian and Turkish Muslims in the first quarter of the twentieth century in the light of the thought of Musa Jarullah, 'Abd Rashid Ibrahimov and Said Nursi. In order to examine the works ofJarullah and Nursi, the researcher adopted an inductive and textual analysis method. The book determines that none of these scholars faced any dilemma between their religious and national identities. After the establishment of the USSR and the Turkish Republic, Muslims were forced to abandon their religious ummah identity and adopt the national identity. Accordingly, the study suggests that the rise of nationalism in Russia and Turkey did not coincide with a voluntary decline in the hold of religion. In addition, the ideas of pan-Islamism were not a recent phenomenon, but it was the continuation of the ummah feelings of Muslims. It was a response of Muslims to Western Imperialism and the spread of ideas of nationalism, secularism and communism. Also, based on the thought of Jarullah and Nursi, the book finds that ideas of calling for unity of Muslims did not bear an anti-Christian character, but it aimed at liberating Muslim nations from their colonial yoke. Moreover, as our research presents, Jarullah and Nursi were optimistic at the prospects of Islamic Union even during decisive years for the Muslim world, when the caliphate was abolished in 1924 and almost all Muslims lands were colonized by Western powers. Consequently, the research book suggests that Islam did not lose its importance in political as well as social lives of Russian and Turkish Muslims. Therefore, the so-called "universal sociological theory" of Hans Kohn is not applicable to the cases of Russian and Turkish Muslims.